Splenogonadal Fusion in Children: A Rare Entity Mimicking Inguinal Tumor. (June 2020) - Guney, Isa Burak; Temiz, Abdulkerim; Oksuzler, Mahmut; Alkan, Murat
Abstract : Abstract: Splenogonadal fusion (SGF) is a rare congenital malformation, which can be of a continuous or discontinuous type. It is characterized by splenic tissue fused with gonadal tissue. Because it lacks characteristic features, very few cases of SGF have been diagnosed preoperatively. Herein, we present a case with left side SGF who was diagnosed by 99m Tc-nanocolloid spleen scintigraphy.